The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/su11030888
|View full text |Cite
|
Sign up to set email alerts
|

Financial Resources for the Circular Economy: A Perspective from Businesses

Abstract: In recent years, a number of case studies of the circular economy in business have been analysed by academics. However, some areas of research are little explored at the micro level, such as the study of the characteristics of the financial resources applied to investments to introduce circular activities in businesses. Therefore, the main objective of this study is to define the resources applied to circular activities by firms. To describe the influence of financial resources on achieving a more advanced cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 132 publications
3
57
0
1
Order By: Relevance
“…Tiwari et al [53] showed that providing small businesses with loans at concessionary interest rates increased their access to finance hence boosted their performance. Further, Aranda-Usón et al [54] found that increasing the availability and quality of sources of finance stimulated the implementation of circular economy initiatives in businesses. Hence our second hypothesis: Hypothesis 2.…”
Section: Access To Finance and Smes' Sustainabilitymentioning
confidence: 99%
“…Tiwari et al [53] showed that providing small businesses with loans at concessionary interest rates increased their access to finance hence boosted their performance. Further, Aranda-Usón et al [54] found that increasing the availability and quality of sources of finance stimulated the implementation of circular economy initiatives in businesses. Hence our second hypothesis: Hypothesis 2.…”
Section: Access To Finance and Smes' Sustainabilitymentioning
confidence: 99%
“…However, the statistics obtained for this variable indicate that it is necessary to regulate the relationship between operational units, their management and coordination mechanisms considering the Env information in order to make the courses of action of the whole system homologous. Coordination (Crd) has also been dealt with in some contributions [17,21,29]; however, it was not identified that this function is part of the dynamics in RAMSAR sites from an integral vision and that complements the tasks of the management processes. In contrast, the proposed model suggests integrating control and regulatory mechanisms to mitigate environmental changes and allow operations at the sites under study to be congruent with the context in which they operate.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, statistical analysis is highlighted in particular by means of PLS-PM, because it has been used to study multiple factors such as how financial resources [29,30], intellectual capital [31,32], and supply chain [17,[33][34][35], influence in sustainability. Also, from a causal perspective, Butler and Adamowski [11] emphasise that interventions based on group modelling can engage stakeholders with the consequence of sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for companies to collaborate is to share the burden of environmental investment, thereby reducing business risk. [55] The following propositions thus emerge: Proposition 4 (P4). The introduction of sustainability must be associated with a strategic evolution of the value proposition, through the transition to a sustainable business model.…”
Section: From Traditional To Sustainable Business Modelsmentioning
confidence: 99%